The age composition of populations of Crataegus ambigua in the natural conditions of Mangyshlak - Duysenova, N.I.; Imanbaeva, А.А.; Tuyakova, А.Т.; Kopbaeva, G.B. (KSU publ., 2017)
In article results of studying of age structure of populations of Crataegus ambigua are given in gorges of Mangystau Region. It is revealed that populations of Crataegus ambigua in natural populations are characterized by different age structure and a state. Hawthorn populations in the gorge Karasay, Akmysh, Kezim and Tulkili Sai it is possible to characterize as the young developing with prevalence the pre-generative of individuals; in gorges Kendirly, Zhemsemsay and Sultan Epe — as unstable and restored after a long drought; in gorges Samal and Emdikorgan — as steady middle-aged with prevalence of young and middle-aged generative plants; in the gorge Karakosayym — as degrading and unstable. Additional security actions in gorges Karakozayym, Kendirly, Zhemsemsay and to Sultan Epe are necessary for preservation of populations of a rare and endemic plant a hawthorn doubtful and restoration of a condition of populations.
Маңғышлақ табиғи жағдайындағы күмəнді долана популяциясының жастық құрамы
Возрастной состав популяций боярышника сомнительного в природных условиях Мангышлака
Keywords: Mangyshlak; Crataegus ambigua; populations; age structure; rare species